PENERAPAN PROGRAM DOUBLE TRACK UNTUK MENCETAK JIWA ENTERPRENEUR - Firman, Firman (Jurnal Edueco, 2025)
This study aims to determine the implementation of the double-track program by Cake Salakilo in SMA Negeri 3 Balikpapan and SMA Negeri 5 Balikpapan. The purpose was to determine the implementation system, obstacles, main objectives, and supporting factors related to the double-track programme. The research method used was a qualitative method that takes a case study research approach and is descriptive. The main data sources include interviews, observations, and documentation. In the Implementation system, there are several supporting factors in the double-track implementation process that encourage students to become entrepreneurs, such as support and motivation from teachers and parents, as well as adequate facilities and infrastructure at Cake Salakilo to encourage students to participate in activities. In addition to supporting factors, researchers also found obstacles such as inadequate facilities and infrastructure at school, which hindered students from exploring their creativity. The purpose of implementing a Double Track in schools is to gain knowledge and skills on how to be an entrepreneur and to realize the desires of students who later want to be entrepreneurs. Keywords: Implementation, Double Track, Entrepreneur